Physical activity as treatment for alcohol use disorders (FitForChange): study protocol for a randomized controlled trial - Mats Hallgren; Victoria Andersson; Örjan Ekblom; Sven Andréasson (Trials, 2018)
Abstract Background Help-seeking for alcohol use disorders (AUDs) is low and traditional treatments are often perceived as stigmatizing. Physical activity has positive effects on mental and physical health which could benefit this population. We propose to compare the effects of aerobic training, yoga, and usual care for AUDs in physically inactive Swedish adults. Methods This is a three-group, parallel, single-blind, randomized controlled trial (RCT). In total, 210 adults (aged 18–75 years) diagnosed with an AUD will be invited to participate in a 12-week intervention. The primary study outcome is alcohol consumption measure by the Timeline Follow-back method and the Alcohol Use Disorders Identification Test (AUDIT). Secondary outcomes include: depression, anxiety, perceived stress, sleep quality, physical activity levels, fitness, self-efficacy, health-related quality of life, and cognition. Blood samples will be taken to objectively assess heavy drinking, and saliva to measure cortisol. Acute effects of exercise on the urge to drink alcohol, mood, and anxiety will also be assessed. Discussion The treatment potential for exercise in AUDs is substantial as many individuals with the disorder are physically inactive and have comorbid health problems. The study is the first to assess the effects of physical activity as a stand-alone treatment for AUDs. Considerable attention will be given to optimizing exercise adherence. Both the feasibility and treatment effects of exercise interventions in AUDs will be discussed. The Ethical Review Board (EPN) at Karolinska Institutet has approved the study (DNR: 2017/1380-3). Trial registration German Clinical Trials Register, ID: DRKS00012311. Registered on 26 September 2017.